Histology of 24 organs from Asian elephant calves (Elephas maximus) - Thitaram, Chatchote; Matchimakul, Pitchaya; Pongkan, Wanpitak; Tangphokhanon, Wasan; Maktrirat, Raktham; Khonmee, Jaruwan; Sathanawongs, Anucha; Kongtueng, Piyamat; Nganvongpanit, Korakot (PeerJ, 2018)
Background Elephants are the largest and heaviest living terrestrial animals, but information on their histology is still lacking. This study provides a unique insight into the elephant’s organs and also provides a comparison between juvenile Asian elephants and adult Asian elephants or other species. Here we report on the histological structure of 24 organs, including the skin, brain (cerebrum, cerebellar hemisphere, vermis, thalamus, midbrain), spinal cord, sciatic nerve, striated skeletal muscle, cardiac muscle, bone (flat bone and long bone), cartilage (hyaline cartilage and fibrocartilage), heart (right atrium, right ventricle), blood vessels (aorta, pulmonary artery and caudal vena cava), trunk, trachea, lung, tongue, esophagus, stomach, small intestine (duodenum, jejunum, ileum), large intestine (cecum, colon, rectum), liver and pancreas, kidney, ovary, uterus (body and horn) and spleen of two juvenile Asian elephants. Methods Tissue sections were stained with Harris’s hematoxylin and eosin Y. Results While almost all structures were similar to those of other species or adult elephants, some structures were different from other mammalian species, such as: plexiform bone was found in flat bone only; a thin trachealismuscle was observed in the trachea; and no serous or mucinous glands were found in the submucosa of the trachea. Discussion Histological information from various organs can serve as an important foundation of basal data for future microanatomical studies, and help in the diagnosis and pathogenesis in sick elephants or those with an unknown cause of death.
Keywords: Elephant; Histology; Microanatomy; Tissue; Organ